Physiological responses at the lactate-minimum-intensity with and without prior high-intensity exercise - Zagatto, Alessandro Moura [UNESP]; Padulo, Johnny; Silva, A. R.S.D.; Müller, Paulo de Tarso Guerrero; Miyagi, Willian Eiji [UNESP]; Gobatto, Claudio Alexandre (Taylor & Francis, 2016)
This study examined the physiological responses during exercise-to-exhaustion at the lactate-minimum-intensity with and without prior high-intensity exercise. Eleven recreationally trained males performed a graded exercise test, a lactate minimum test and two constant-load tests at lactate-minimum-intensity until exhaustion, which were applied with or without prior hyperlactatemia induction (i.e., 30-s Wingate test). The physiological responses were significantly different (P < 0.05) between constant-load tests for pulmonary ventilation (Formula presented.), blood-lactate-concentration ([La−]), pH, bicarbonate concentration ([HCO3]) and partial pressure of carbon dioxide during the initial minutes. The comparisons within constant-load tests showed steady state behaviour for oxygen uptake and the respiratory exchange ratio, but heart rate and rating of perceived exertion increased significantly during both exercise conditions, while the (Formula presented.) increased only during constant-load effort. During effort performed after high-intensity exercise: (Formula presented.) , [La−], pH and [HCO3] differed at the start of exercise compared to another condition but were similar at the end (P > 0.05). In conclusion, the constant-load exercises performed at lactate-minimum-intensity with or without prior high-intensity exercise did not lead to the steady state of all analysed parameters; however, variables such as [La−], pH and [HCO3] – altered at the beginning of effort performed after high-intensity exercise – were reestablished after approximately 30 min of exercise.
Keywords: Exercise physiology; kinetic of lactate; metabolic demand; oxygen uptake; workload